Exploring the Potential of Pharmacy Technician-Led Medication Reconciliation Programs in Reducing Hospital Readmissions for Patients with Polypharmacy: A Qualitative Study in Saudi Arabia - Salwa Mudhhi Fahad Alanazi; Maryam Mubarak Farj Alanazi; Eman Hadi Alanaz; Hala Fazzaa Mohammed Aldhafeeri; Abdullah Hamdan Saud Alshammari; Munirah Saad Obaid Almutairi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This qualitative study explored the potential of pharmacy technician-led medication reconciliation programs in reducing hospital readmissions for patients with polypharmacy in Saudi Arabia. Methods: Semi-structured interviews were conducted with 25 pharmacy technicians, 15 pharmacists, and 10 physicians across 5 hospitals in major cities of Saudi Arabia. Thematic analysis was used to identify key themes. Results: Three main themes emerged: 1) Pharmacy technicians are well-positioned to lead medication reconciliation efforts given their technical expertise and time availability compared to pharmacists and physicians; 2) Medication reconciliation reduces discrepancies and errors that contribute to readmissions for polypharmacy patients; 3) Barriers include limited technician prescribing authority, incomplete patient records, and inconsistent reconciliation procedures across care transitions. Conclusions: Pharmacy technician-led medication reconciliation programs show promise for reducing hospital readmissions among patients with polypharmacy in Saudi Arabia. Addressing identified barriers and establishing standardized procedures are important for maximizing impact. Further research should quantitatively evaluate outcomes of these programs.